2019
DOI: 10.1016/j.heliyon.2019.e02242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acorn flour on the physico-chemical and sensory properties of biscuits

Abstract: The aim of the work was to explore the feasibility of using acorn flour as a novel and healthy ingredient in biscuits. The physico-chemical characteristics of acorn flour obtained from three different Quercus species were compared. Acorns of Quercus coccifera L. were the most antioxidant and were therefore used for preparing biscuits at two levels of addition, 30 and 60 g 100 g À1 on wheat flour basis. The physico-chemical and sensory characteristics of the obtained biscuits were then assessed. Acorn-added bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 38 publications
7
43
3
3
Order By: Relevance
“…Another study carried out by Korus et al [28], concerning the addition of acorn flour in GF biscuits, demonstrated a higher phenolics content, antioxidant activity, and oxidative stability, in comparison with biscuits without acorn flour from the control. The previous study reinforced the fact that a progressive incorporation of acorn flour enhances the results, which Pasqualone et al [36] showed as well.…”
Section: Control A23% A35%supporting
confidence: 76%
“…Another study carried out by Korus et al [28], concerning the addition of acorn flour in GF biscuits, demonstrated a higher phenolics content, antioxidant activity, and oxidative stability, in comparison with biscuits without acorn flour from the control. The previous study reinforced the fact that a progressive incorporation of acorn flour enhances the results, which Pasqualone et al [36] showed as well.…”
Section: Control A23% A35%supporting
confidence: 76%
“…Quercus ilex L. oil showed a significantly higher level of esters, alcohols, and acids of the acetic series, which was likely indicative of over‐mature or degraded raw material. Similar compounds from fermentation processes were also found in biscuits enriched with acorn flour 4 . Finally, QS had the lowest amount of alcohols, esters, and acetic acid.…”
Section: Resultssupporting
confidence: 66%
“…are considered nutritionally valuable and have been used for thousands of years wherever oak trees were found, being a good source of carbohydrates, proteins, and fat 1 . Milled to flour, acorns have recently been proposed as functional ingredients for producing bread and biscuits 2‐4 . The lipid fraction of acorns is also recognized for having high nutritional quality because it is rich in unsaturated fatty acids and in bioactive compounds, such as polyphenols, tocopherols, and sterols 5‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…Produk millet crispy termasuk ke dalam golongan biskuit dimana mempunyai ciri-ciri renyah dan kering (Pasqualone, 2019). Biskuit merupakan camilan yang dibuat dengan pencampuran bahan kering seperti tepung dan bahan basah seperti telur (Biguzzi, 2015).…”
Section: Pendahuluanunclassified